Drug-induced Nephropathy and Molecular Patterns of Oxidative Stress - Lee, V.; Bakirova, R.; Muravlyova, L.; Turkhanova, Zh.; Rakhmetova, A. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Drug-induced kidney disorder is a frequent adverse event which contributes to morbidity and even incapacitation. Our current knowledge of drug-induced kidney disease is limited due to varying definitions of kidney injury, incomplete assessment of concurrent risk factors, and lack of long term outcome reporting. AIM: The discovery and development of novel biomarkers and local (renal) response mechanisms, which can diagnose kidney damage earlier and more accurately, are needed for effective prevention of drug-induced nephrotoxicity. METHODS: Forty patients from 22 to 50 years old with drug-induced nephropathy (43 females, 27 males) were included in the study. The determination of oxidative stress modifications as advanced oxidation protein products (AOPPs), protein reactive carbonyl derivatives (PRCD), methylglyoxal, and catalase (CAT) level were assayed. AOPP was rated in blood plasma through the Witko-Sarsat (1996) method, PRCD by Levine (2000) method, methylglyoxal through the Racker (1963) method, CAT was evaluated with Koroljuk (1988) and Aebi (1984) methods. Conditionally, 30 healthy-matched persons were included in the control group. RESULTS: In psychotropic and nonsteroidal anti-inflammatory drugs (NSAID) drug-induced nephropathy patients, there was a tendency to increase the concentration of AOPP in blood plasma, PRCD, and methylglyoxal in erythrocytes relative to the upper limits of normal ranges. Moreover, there was a significant decrease of the CAT level in blood plasma relative to the upper limits of normal ranges. CONCLUSION: Thus, the results of the present study permit us to draw the following conclusions. The patients with psychotropic and NSAIDs drug-induced nephropathy have increased level of oxidative stress products and increased neutrophil gelatinase-associated lipocalin level even in normal eGFR. The mechanisms that lead to the development of oxidative stress and the production of modified proteins are different in patients treated with different drugs.
Keywords: oxidative stress; drug-induced nephropathy; modified proteins; nonsteroidal anti-inflammatory drugs; psychotropic drugs